Metallurgy of welding - Lancaster, J. F. (Abington Pub., 1999)
A new edition of a well established and respected textbook from an author who is a recognised authority in this field. Joining techniques are one of the key technologies in materials engineering and this book provides comprehensive coverage of the subject. It is intended for undergraduate and graduate students of metallurgy, as well as those attending specialist welding courses. It is also a valuable source of reference for practising engineers and metallurgists concerned with joining processes. The text covers the metallurgical changes that take place during the welding process, the properties of welded joints, defects associated with welding and the behaviour of welded joints in service. There is a chapter devoted to joints between metals and ceramics, and on the use of structural adhesives. The various techniques used in microwelding and the joining of solid-state devices to printed circuit boards are briefly described. In addition to revising and updating the text throughout the author has made some specific alterations and additions to the book:Brittle and ductile behaviour of solids, ductile francture, and the velocity of crack propogation are now included in the section on Fracture; Friction stir welding in now included; There is an additional chapter on adhesive bonding which includes bonding; forces, polymer chemistry, types of adhesive, production technology, quality control and applications; The section on heat flow has been expanded and includes worked examples; A section on weld defects and the evaluation of non-destructive tests has been added; A section on the welding metallurgy of aluminium-lithium alloys has been added; A new section describes major structural failure in such catastrophes as the 'Alexander L Kielland' accident and the Kobe earthquake, and considers the role of welding in such failures.